2023
DOI: 10.1093/haschl/qxad013
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic telehealth flexibilities for buprenorphine treatment: a synthesis of evidence and policy implications for expanding opioid use disorder care in the United States

Abstract: Buprenorphine is a highly effective treatment for opioid use disorder and a critical tool for addressing the worsening U.S. overdose crisis. However, multiple barriers to treatment - including stringent federal regulations - have historically made this medication hard to reach for many who need it. In 2020, under the COVID-19 Public Health Emergency, federal regulators substantially changed access to buprenorphine by allowing prescribers to initiate patients on buprenorphine via telehealth without first evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
3
4
0
Order By: Relevance
“…Our findings from the patient perspective also align with previous studies, which have found patients appreciated having options and the flexibility telemedicine provided in the context of competing demands and priorities in their lives [ 16 ]. However, though telemedicine may offer distinct benefits, particularly in helping patients overcome barriers to appointment attendance, a notable finding in this study was that patients’ views on the appropriateness of telemedicine visits centered around an individual’s stage of recovery, with the perceived need for structure and accountability early in treatment as a key concern.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings from the patient perspective also align with previous studies, which have found patients appreciated having options and the flexibility telemedicine provided in the context of competing demands and priorities in their lives [ 16 ]. However, though telemedicine may offer distinct benefits, particularly in helping patients overcome barriers to appointment attendance, a notable finding in this study was that patients’ views on the appropriateness of telemedicine visits centered around an individual’s stage of recovery, with the perceived need for structure and accountability early in treatment as a key concern.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our results support telemedicine as an acceptable method for providing office-based buprenorphine treatment for individuals with OUD and demonstrate how it can improve access to and retention in care for many patients. These findings align with those from prior studies indicating that the COVID-19-related regulatory flexibilities around the use of telemedicine for office-based buprenorphine treatment should be maintained [ 16 , 20 ]. In addition, patients in this study–the majority of whom were publicly-insured–expressed a desire to have a combination of telemedicine and in-person visits moving forward.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Continued efforts to increase COVID-19 flexibilities for methadone take-homes and facilitating the initiation of buprenorphine via telehealth, which has been found to facilitate initiation and retention in MOUD, are strategies that can help facilitate long-term outcomes in these treatments. 65,66 Expanding methadone to other treatment settings, including mobile health vans (which have recently launched in NY) 67,68 and office-based practices as is done in many non-US settings, 69 and which has been proposed by recent legislation, may also improve MMT access and continuity. Importantly, ensuring connections to harm reduction programs is also critical for ensuring reduced overdose among this population.…”
Section: Discussionmentioning
confidence: 99%